Effect of heat stress on carcass and meat quality of indigenous sheep of Bangladesh - Rana, MS; Hashem, MA; Akhter, S; Habibullah, M; Islam, MH; Biswas, RC (Bangladesh Journal of Animal Science, 2014)
The research was conducted to study the effect of heat stress on carcass characteristics and meat quality in indigenous sheep. Nine sheep were divided into three groups which were almost similar in age, sex and weight. Three groups were divided as zero hour (T0), four hours (T4) and eight hours (T8) heat exposure to direct sunlight. During experimental period temperaturehumidity index (THI) value was calculated as 27.09 which indicated T4 and T8 groups were subjected to heat stress condition for at least four hours and eight hours respectively every day. Slaughter weight, body length and heart girth had no significant difference among the treatment groups. Dry matter, ash and ether extract had no significant difference (p>0.05) among the treatment groups but crude protein were increased with the increase of heat stress from T0 to T8 group (p<0.05). Drip loss was increased (p<0.05) in non-exposure group than treated groups but there is no significant result (p>0.05) found in pH and cooking loss. Carcass weight and eye muscle area had no significant difference (p>0.05) among the treatment groups but dressing percentage was decreased with the increase of time in heat treated groups (p<0.01). Significant difference (p<0.05) were found in weight of heart, kidney, lung + trachea and pluck between control and heat treated groups. The significant difference (p>0.05) in empty gut was found in gut with content and gut fill in heat treated groups. It can be concluded that heat stress had significant changes on carcass characteristics and meat quality of indigenous sheep. DOI: http://dx.doi.org/10.3329/bjas.v43i2.20717 Bang. J. Anim. Sci. 2014. 43 (2): 147-153